Environmental crisis and urban planning - Khan, Zakiya Tasneem, 1952- (New Delhi : Ashish Pub. House, 1992)
Study of Bilaspur City, Madhya Pradesh.
Includes bibliographical references (p. [233]-243) and index.
Keywords: Urbanization -- India; Social ecology -- India; Urban ecology (Sociology) -- India